Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

Mucoadhesive nanofibers for ocular drug delivery: mechanisms, design strategies, and applications - Nimeet Desai; Helen E. Colley; Yamini Krishna; Lucy A. Bosworth; Victoria R. Kearns (Drug Delivery and Translational Research, 2026)
Delivering drugs effectively to the ocular surface is challenging due to rapid clearance mechanisms, including blinking, tear turnover, and protective barriers of the conjunctival and corneal epithelium. As a result, conventional options such as eye drops often fail to provide sustained therapeutic effects and require frequent dosing, leading to reduced patient compliance. Mucoadhesive nanofiber systems offer a promising solution by enhancing drug retention and enabling controlled release at the ocular surface. These nanofibers, produced primarily through electrospinning, provide a high surface area, tunable mechanical properties, and compatibility with mucoadhesive polymers, collectively improving drug bioavailability, extending residence times, and minimizing systemic side effects. This review comprehensively explores the fundamentals of mucoadhesion, including the structural and compositional characteristics of ocular mucosal surfaces and the molecular interactions essential for optimized drug delivery. It examines advanced strategies for incorporating mucoadhesive features into nanofibers, such as polymer blending, surface modification, and molecular imprinting, and assesses their influence on therapeutic outcomes. Finally, recent advancements and their potential for clinical translation are discussed. By presenting a thorough analysis of current techniques and emerging innovations, this review aims to guide researchers in developing next-generation mucoadhesive nanofiber platforms that improve therapeutic efficacy and patient compliance in ocular drug delivery. Graphical Abstract

Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

Suspended sediment properties and visual clarity of the Manawatū River, New Zealand - Rob J. Davies‐Colley; Andrew O. Hughes; Arman Haddadchi; John R. Dymond; Simon S. Vale; Hugh G. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
Studies of river suspended sediment typically focus on mass loads with little attention devoted to sediment properties such as particle size distribution (PSD) or light attenuation. However, environmental behaviour and ecological effects of suspended sediment vary greatly with particle properties. Visual clarity is a particularly important attribute of waters that is strongly affected by particle properties. We studied the relationship between visual clarity and suspended sediment in the Manawatū River – by combining event auto‐sampling with long‐term state‐of‐environment monitoring. We fractionated stormflow samples into sand and ‘mud’ (silt + clay) by wet‐sieving at 63 μm, and the mud fraction was further analysed for organics, PSD and light beam attenuation (which controls visual clarity). Light beam attenuation correlated very closely with high‐frequency field turbidity – providing an absolute optical calibration. The ratio of light beam attenuation to mass concentration (known as ‘optical cross‐section’) averaged about 0.5 m 2 /g – somewhat higher than expected for silt particles in the measured size range, probably due to plate‐shaped clays. The visual clarity regime, estimated from field turbidity, was consistent with monthly direct observations. Our study illustrates how certain sediment ‘quality’ metrics can usefully extend sediment monitoring applications, and we encourage closer integration of sediment and water quality monitoring.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Community volunteer assessment of recreational water quality in the Hutt River, Wellington - Amanda E. Valois; Juliet R. Milne; Mark W. Heath; Rob J. Davies‐Colley; Emily Martin; Rebecca Stott (New Zealand Journal of Marine and Freshwater Research, 2020)
Water is an important component of many recreational opportunities and New Zealand invests significant resources in recreational water quality (RWQ) monitoring to assess risks to public health. However, monitoring primarily focuses on microbiological hazards and RWQ is considerably broader than this. The goal of this study was to take a comprehensive approach to evaluating RWQ while exploring the potential for greater public involvement in monitoring. A popular river swimming site was co‐monitored weekly by volunteers and a council field officer. The attributes monitored–water temperature, visual clarity, benthic cyanobacteria and filamentous periphyton cover, E. coli and rubbish–were identified from a volunteer workshop. There was good concordance between volunteer and council data suggesting that volunteer measurements can be considered reliable. This highlights the potential for volunteers, with professional support, including training and quality assurance, to extend council RWQ surveillance to additional monitoring sites while improving public engagement on water management.

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Optical closure in lakes with contrasting extremes of reflectance - C. L. Gallegos; R. J. Davies-Colley; M. Gall (Limnology and Oceanography, 2008)
We measured inherent and apparent optical properties and computed ‘optical closure’ in four lakes on the South Island of New Zealand, ranging very widely in reflectance. Optical properties were measured by modern instruments deployed from boats, with supporting laboratory measurements on water samples. The radiative transfer model, Hydrolight, was used with measured inherent optical properties to predict characteristics of the light field for comparison with field measurements. Two glacier‐fed lakes were strongly light‐scattering and weakly light‐absorbing, with optical properties dominated by glacial flour. In marked contrast, two humic‐stained wetland lakes were strongly light‐absorbing and weakly light‐scattering, with optical properties dominated by colored dissolved organic matter. Very good optical “closure” (i.e., agreement of modeled with measured characteristics of the light field) was obtained for all apparent optical properties examined in all but the most strongly light‐scattering lake. Closure was achieved when systematic spectral bias in absorption in this lake, possibly caused by multiple scattering in the field absorption meter, was corrected using laboratory absorption measurements. The highest and lowest measured and modeled water‐leaving radiances exceeded the previous range for such studies by a factor of 5. The good optical closure observed over a very wide (200‐fold) range of reflectance increases confidence in our ability to specify inputs for radiative transfer modeling while highlighting the enduring challenge of accurately measuring absorption in highly scattering waters and backscattering in highly absorbing waters.

Reproductive ecology of the azooxanthellate coral Tubastraea coccinea in the Equatorial Eastern Pacific: Part V. Dendrophylliidae - P. W. Glynn; S. B. Colley; J. L. Maté; J. Cortés; H. M. Guzman; R. L. Bailey; J. S. Feingold; I. C. Enochs (Marine Biology, 2008)

Reproductive ecology of the azooxanthellate coral Tubastraea coccinea in the Equatorial Eastern Pacific: Part V. Dendrophylliidae - P. W. Glynn; S. B. Colley; J. L. Maté; J. Cortés; H. M. Guzman; R. L. Bailey; J. S. Feingold; I. C. Enochs (Marine Biology, 2008)

Ecoregional differences in macrophyte and macroinvertebrate communities between Westland and Waikato: Are all New Zealand lowland streams the same? - I. C. Duggan; K. J. Collier; P. D. Champion; G. F. Croker; R. J. Davies‐Colley; P. W. Lambert; J. W. Nagels; R. J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2002)
We characterised water chemistry, aquatic habitat, macrophytes, and invertebrate assemblages in eight lowland streams—five in Westland, South Island, and three in the Waikato, North Island, New Zealand. Factors influencing invertebrate community structure over large (between ecoregions) and small (within an ecoregion) spatial scales were investigated. The Westland sites had generally lower nutrient concentrations, conductivity, and water clarity, and coarser substrates than the Waikato sites, reflecting differences in geological history, hydrology, and land‐use intensity. The macrophyte communities in each region were very different in species composition and structure, but seasonal abundance patterns in both regions were fairly typical of New Zealand streams in general. Alien obligate submerged macrophyte species were absent from the Westland lowland stream sites, and may partly reflect the isolated nature of this region where colonisation by asexual macrophytes would be difficult. Waikato stream invertebrate faunas were dominated by molluscs (mainly Potamopyrgus ) and crustaceans (mainly amphipods), whereas Epheme‐roptera, Trichoptera, and Coleoptera taxa dominated the Westland stream faunas. The overall structure of invertebrate assemblages appeared to be influenced by a combination of regional differences in substrate type, nutrient concentrations, water clarity, and macrophyte cover. Westland streams with more upstream pastoral development had higher proportions of molluscs than those with predominantly forested or scrub catchments. Our study suggests that large‐scale ecoregional differences may override smaller‐scale land‐use effects on lowland stream invertebrate communities, and that management strategies should be developed on an ecoregional basis for lowland stream ecosystems.

Land use effects on habitat, water quality, periphyton, and benthic invertebrates in Waikato, New Zealand, hill‐country streams - John M. Quinn; A. Bryce Cooper; Robert J. Davies‐Colley; J. Christopher Rutherford; R. Bruce Williamson (New Zealand Journal of Marine and Freshwater Research, 1997)
Water quality, habitat, and biota were compared during spring amongst c. 100 m reaches on 11 streams draining pasture, native (podocarp‐broadleaf) forest, and exotic pine forest established on pasture 15 years previously. Differences were greatest between the pasture and native forest streams. Only 1–3% of incident light reached native and pine forest streams whereas 30% reached pasture streams. Pasture streams had 2.2°C higher mean temperature than the native streams, and 5‐fold higher nitrate, 30‐fold higher algal biomass, and 11‐fold higher gross photosynthesis. Native streams were 60% wider than pasture, with pine streams intermediate. Pine and pasture streams had 3‐fold higher suspended solids and fine sediment stored in the streambed than native streams. Woody debris volume was 17‐fold greater in pine than pasture streams, with native streams intermediate. Invertebrate taxa richness did not differ between land uses. Community composition differed most between pasture and native forest, with pine forest streams intermediate. Invertebrate densities were 3‐fold higher in pasture than native streams, mainly because of more chironomids and snails, but mayflies, stoneflies, and caddisflies densities were 2–3‐fold higher in forest streams than pasture.